Façade Elements for Combined Photovoltaic–Solar Thermal Energy Generation and Building Insulation - Krauter, Stefan (Proceedings of the 18th Conference on Passive and Low Energy Architecture, Florianópolis (Brasilien), 7.–9. November 2001, Band 1, S. 275–262)

Software for Simulation of Photovoltaic Systems in Buildings - Krauter, Stefan; Valentin, G. (Proceedings of the 18th Conference on Passive and Low Energy Architecture, Florianópolis (Brasilien), 7.–9. November 2001, Band 1, S. 283–285)

RIO 02 – The World Energy and Climate Event - Krauter, Stefan (Proceedings of the 18th Conference on Passive and Low Energy Architecture, Florianópolis (Brasilien), 7.–9. November 2001, Band. 2, S. 1049–1052)

All-in-one Solar Home System - Krauter, Stefan; Ochs, F. (Proceedings of the ISES 2001 Solar World Congress, Adelaide (Australia), 25–30 November 2001, S.1641–1647)

A Satellite Monitoring System for Remote Renewable Energy Systems in Brazil - Krauter, Stefan; Depping, T.; Ochs, F. (Proceedings of the ISES 2001 Solar World Congress, Adelaide (Australien), 25.–.30 November 2001, S. 1485–1490)

RIO 02 – World Climate and Energy Event - Krauter, Stefan (Proceedings of the ISES 2001 Solar World Congress, Adelaide (Australia), 25–30 November 2001, S. 1473–1480)

On the Specification and Analysis of Protocols in UML-RT - Engels, Gregor; Küster, Jochen; Groenewegen, Luuk

Vergleichsmöglichkeiten für Finanzdienstleistungsangebote im WWW - Kundisch, Dennis; Dzienziol, J.; Eberhardt, M.; Pinnow, M. (WIRTSCHAFTSINFORMATIK)

Enabling eCCRM: Multi-Channel Model and Management for Financial eServices - Kundisch, Dennis; Wolfersberger, P.; Klöpfer, E. (The International Journal on Media Management)

Enabling eCCRM: Content Model and Management for Financial eServices - Kundisch, Dennis; Wolfersberger, P.; Calaminus, D.; Klöpfer, E. (Proceedings of the 34th Hawaii International Conference on System Sciences (HICSS))

Mobile Pricing for Congested UMTS Networks - Kundisch, Dennis; Schell, A. (Proceedings of the International Conference on Internet Computing 2001 (IC))

Kurzlebige Moden oder dominierende Arbeitsgebiete?: Personalpraktiken zwischen Wiedervereinigung und Jahrtausendwechsel - Kabst, Rüdiger (Personalwirtschaft und Organisationskonzepte moderner Betriebe, Beiträge zur Arbeitsmarkt- und Berufsforschung, BeitrAB 252)

Erfolgsfaktoren der Internationalisierung mittelständischer Unternehmen: Internationalisierungsverlauf und Expatriate Management, Paderborn 2001 - Kabst, Rüdiger

Personalmanagement im internationalen Vergleich: The Cranfield Project on International Strategic Human Resource Management - Ergebnisbericht 2000, Paderborn 2001 - Weber, W; Kabst, Rüdiger

A semiparametric fractional autoregressive model - Beran, Jan; Feng, Yuanhua (Statistical Review (Revista de Estatistica))

Supplement to the paper "Iterative plug-in algorithms for SEMIFAR models - definition, convergence and asymptotic properties" - Detailed simulation results - Beran, Jan; Feng, Yuanhua

Gibt es eine Nachfrage nach produktiver Freizeit - Fahr, Rene (Statistisches Bundesamt (Hrsg.), Spektrum Bundesstatistik)

Konstruktion, Implementation und Evaluation komplexer Lehr- Lernarrangements - Fallbeispiele aus Deutschland, Niederlande und Österreich im Vergleich

Lernfelder implementieren. Zur Entwicklung und Gestaltung fächer- und lernortübergreifender Lehr-Lernarrangements im Lernfeldkonzept

Planspiel zur Messebeteiligung. Zur Gestaltung von Lernsituationen im Lernfeldkonzept

Cooperability in Train Control Systems: Specification of Scenarios using Open Nets - Padberg, Julia; Jansen, Lars; Ehrig, Hartmut; Schnieder, E.; Heckel, Reiko (Transactions of the Society for Design and Process Science)

Double Pullback Transitions and Coalgebraic Loose Semantics for Graph Transformation Systems - Heckel, Reiko; Ehrig, Hartmut; Wolter, Uwe; Corradini, Andrea (Applied Categorical Structures)

Roles in Agent-Oriented Modeling - Depke, Ralph; Heckel, Reiko; Küster, Jochen (International Journal of Software Engineering and Knowledge Engineering)
In this paper, we perform such an analysis and identify requirements for a general role concept. We develop such a role concept for a modeling approach based on the UML and graph transformation systems and exemplify its use for the specification (and application) of protocols. Finally, we provide a run-time semantics for roles based on concepts from the theory of graph transformation.

A Coalgebraic presentation of structured transition systems - Corradini, Andrea; Große-Rhode, Martin; Heckel, Reiko (Theoretical Computer Science)

Modelle für automobile Software - Objektorientierte Modellierung von eingebetteten, interaktiven Softwaresystemen im Automobil - Engels, Gregor; Gaulke, Jens; Sauer, Stefan (Forschungsforum Paderborn)
Wie in allen technischen Geräten werden auch im Automobil immer mehr Funktionen durch Softwaresysteme realisiert bzw. gesteuert. Bei einer Entwicklung derartiger Softwaresysteme wird im Rahmen eines ingenieurmäßigen Entwicklungsprozesses zunächst ein Modell erstellt. Hierzu muss eine Modellierungssprache zur Verfügung stehen, die den Modellierer adäquat bei der Erstellung des Modells unterstützt und ein einheitliches Verständnis des Modells ermöglicht.

Kundenbindung mit Electronic Commerce - Bliemel, F; Eggert, A (Roadm@p to E-Business)

Virtuelle Seminare gestalten - Kremer, H.-Hugo; Sloane, Peter F. E. (Handbuch E-Learning: Expertenwissen aus Wissenschaft und Praxis, Grundwerk Dezember 2001)

Wissensforum als Instrument der Lernortkooperation - Dilger, B.; Kremer, H.-Hugo; Sloane, Peter F. E. (Wirtschaft und Erziehung)

Lehrerrolle und Lernfeldkonzept - Kremer, H.-Hugo; Sloane, Peter F. E. (Modernisierung der Berufsbildung in Europa. Neue Befunde der berufs- und wirtschaftspädagogischen Forschung)

Vorbemerkungen - Kremer, H.-Hugo; Sloane, Peter F. E. (Konstruktion, Implementation und Evaluation komplexer Lehr-Lernarrangements - Fallbeispiele aus Deutschland, Niederlande und Österreich im Vergleich)

Fallbeispiel IV: Didaktische Innovationen gestalten - Realisierung fächer- und lernortübergreifender Ausbildungskonzepte - Kremer, H.-Hugo; Sloane, Peter F. E. (Konstruktion, Implementation und Evaluation komplexer Lehr-Lernarrangements - Fallbeispiele aus Deutschland, Niederlande und Österreich im Vergleich)

Fächer- und Lernortübergreifender Unterricht - Maßnahmen zur Förderung beruflicher Handlungskompetenz - Kremer, H.-Hugo; Melke, K.; Sloane, P. F. E. (Lehren und Lernen in der beruflichen Erstausbildung. Grundlagen einer modernen kaufmännischen Berufsqualifizierung)

Vorbereitung auf eine Messebeteiligung - Planspiel 'Marmelade' - Kennerknecht, M.; Kremer, H.-Hugo; Sloane, Peter F. E. (Berufsbildung in Wissenschaft und Praxis)

eCRM – Electronic Customer Relationship Management: Management der Kundenbeziehungen im Internet-Zeitalter

Konzeptionelle Grundlagen des elektronischen Kundenbeziehungsmanagements - Eggert, A (eCRM – Electronic Customer Relationship Management: Management der Kundenbeziehungen im Internet-Zeitalter)

Elektronisches Kundenbeziehungsmanagement (eCRM) - Eggert, A; Fassott, G (eCRM – Electronic Customer Relationship Management: Management der Kundenbeziehungen im Internet-Zeitalter)

Using an XML-capable mailtool for the communication in software development projects - Lohmann, Marc; Wagner, Annika (Proceedings of the Workshop on XML Technologies and Software Engineering (XSE; satellite event of the ICSE 2001), Toronto (Canada))

Using UML models for the Description of Concurrent Behavior in Component Interfaces - Schattkowsky, Tim; Mehner, Katharina; Depke, Ralph (Proceedings of the Workshop on Concurrency Issues of the UML (satellite event of the International Conference on the Unified Modeling Language - UML 2001), Toronto (Canada))

Agent-oriented Modeling with Graph Transformation - Depke, Ralph; Heckel, Reiko; Küster, Jochen (Proceedings of the First international workshop on Agent-oriented software engineering (AOSE 2000), Limerick (Ireland))

"Separation of Concern" mit Rollen, Subjekten und Aspekten - Depke, Ralph; Mehner, Katharina (Proceedings of the workshop on Aspektorientierung - Workshop der GI-Fachgruppe 2.1.9 Objektorientierte Software-Entwicklung (2001), Paderborn (Germany))

Enhancing UML-RT Concepts for Behavioral Consistent Architecture Models - Engels, Gregor; Küster, Jochen (Proceedings of the 1st Workshop on Describing Software Architecture with UML (satellite event of the ICSE 2001), Toronto (Canada))

Identifiying Semantic Dimensions of (UML) Sequence Diagrams - Hendrik Hausmann, Jan; Küster, Jochen; Sauer, Stefan (Proceedings of the workshop on Practical UML-Based Rigorous Development Methods - Countering or Integrating the eXtremists (pUML, colocated with the UML 2001), Toronto (Canada))
Although UMS sequence diagrams are widely used in practical software development, there is still a great demand for improvements. Their use both within and outside the standard interpretation of the UML specification is not seldom confused because different interpretations for sequence diagrams exist without means to distinguish between them. Furthermore, alternative sequence diagram notations with more syntactical features and different semantics still have a big influence and are readily used (explicitly as well as implicitly) alongside UML's sequence diagrams.

Behavioral Constraints for Visual Models - Heckel, Reiko; Küster, Jochen (Proceeding of the Workshop on Graph Transformation and Visual Modelling Techniques (GT-VMT 2001, satellite event of the ICALP 2001), Heraklion (Greece))

Visualization and Debugging of Concurrent Java Programs with UML - Mehner, Katharina; Weymann, Bernd (Proceedings of the Workshop on Software Visualization (satellite event of the International Conference on Software Engineering - ICSE 2001), Toronto (Canada))

Untersuchung und Weiterentwicklung linearer piezoelektrischer Schwingungsantriebe - Hemsel, Tobias

Improving Goodput by Relaying in Transmission-Power-Limited Wireless Systems - Mengesha, Seble; Karl, Holger; Wolisz, Adam (GI Jahrestagung (1))

Increased thermal budget for selectively doped heterostructures by employing AlAs/GaAs superlattices - Reuter, Dirk; Meier, Cedrik; Álvarez, M. A. Serrano; Wieck, A. D. (Applied Physics Letters)

Players, Playthings and Patterns: Three Stages of Heteronomy in Beckett's Mature Drama - Tönnies, Merle (Samuel Beckett Today / Aujourd'hui: Endlessness in the Year 2000 / Fin sans fin en l'an 2000)

The Limits of Defining Power in Terms of Exclusion - Tönnies, Merle (Common Ground? Crossovers between Cultural Studies and Postcolonial Studies)

Schwingungsanalyse verstimmter Schaufelkränze mit Reibelementen - Panning, Lars; Sextro, Walter; Popp, Karl (Schwingungen in rotierenden Maschinen VI SIRM, Referate der Tagung in Wien)